Chitosan-Based Nanogels: Synthesis and Toxicity Profile for Drug Delivery to Articular Joints - Seng Manivong; Araceli Garcia Ac; Shunmoogum A. Patten; Julio C. Fernandes; Mohamed Benderdour; Xavier Banquy; Florina Moldovan; Valérie Gaëlle Roullin (Nanomaterials, 2022)
One important challenge in treating avascular-degraded cartilage is the development of new drugs for both pain management and joint preservation. Considerable efforts have been invested in developing nanosystems using biomaterials, such as chitosan, a widely used natural polymer exhibiting numerous advantages, i.e., non-toxic, biocompatible and biodegradable. However, even if chitosan is generally recognized as safe, the safety and biocompatibility of such nanomaterials must be addressed because of potential for greater interactions between nanomaterials and biological systems. Here, we developed chitosan-based nanogels as drug-delivery platforms and established an initial biological risk assessment for osteocartilaginous applications. We investigated the influence of synthesis parameters on the physicochemical characteristics of the resulting nanogels and their potential impact on the biocompatibility on all types of human osteocartilaginous cells. Monodisperse nanogels were synthesized with sizes ranging from 268 to 382 nm according to the acidic solution used (i.e., either citric or acetic acid) with overall positive charge surface. Our results demonstrated that purified chitosan-based nanogels neither affected cell proliferation nor induced nitric oxide production in vitro. However, nanogels were moderately genotoxic in a dose-dependent manner but did not significantly induce acute embryotoxicity in zebrafish embryos, up to 100 µg∙mL−1. These encouraging results hold great promise for the intra-articular delivery of drugs or diagnostic agents for joint pathologies.